KAJIAN PRINSIP PERKAWINAN MENURUT UU NO. 1 TAHUN 1974 DALAM PERSPEKTIF HUKUM ISLAM1 Oleh: Mohammad R. Hasan 2 - Muhammad Wahyudi; Fauzia Novita Sari; Qofifa Sari (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
The purpose of this research is to find out how the principle of marriage according to Law no. 1 of 1974 concerning the Principles of Marriage and how marriage according to Law no. 1 of 1974 in the perspective of Islamic law. By using normative juridical research methods, it can be concluded: 1. The community views a sacred event as a marriage. Marriage is the first step to form a family, which in turn is a collection of families that will form the citizens of a society that will eventually become a country. It can be said that if the marriage is carried out in accordance with religious regulations and laws, it is certain that good families will be formed. In turn the country will be good. The principle of marriage that lives and grows in society according to Law no. 1 of 1974 requires the approval of both parties (prospective bride and groom), as a condition/proposal, the awarding of a dowry, in the marriage contract, witnessed by 2 (two) witnesses, the guardian of the party, the prospective bride and every marriage is recorded according to statutory regulations -applicable invitations. 2. The mi balik (ulama) view or think that marriage is a suggestion which results in being sunnah, obligatory, makruh and unlawful. Marriage is a holy (sacred) event that begins with